Study on the relationship between leader‘s personality and employees work satisfaction - Nurfaridatul Aini, Abdullah (2013)
This research is aimed to investigate the relationship between leader‘s personality and employees work satisfaction. 103 employees from the electronic industry in Kelantan participated in the survey questionnaire. There are two variable in this study which are independent variables (Leader‘s personality) and dependent variable (employee work satisfaction). Reliability test is used to identify whether the variable is reliable or not. The results of Cronbach‘s Alpha for all variables shows that the involved variables are reliable ranging from 0.70 to 0.907. Single mean t -test is used to identify the level of employee work satisfaction which shows a high value of 3.22. Pearson correlation results indicate that the personality of leader (extraversion, agreeableness, openness to experiences and conscientiousness) has a positive relationship with the employee work satisfaction, while only Neuroticism personality has a negative relationship with employee work satisfaction. Finding of this study is beneficial to employer to understand how important their personality style to the work satisfaction of employees, as well as to prevent recurrences of dissatisfaction among employees in an organization.